Banding on Adolescents: Is Molar Band Height Different than Clinical Crown Height? - Kafle, Dashrath; Agarwal, Aradhana; Shrestha, Sita; Adhikari, Biplov (Orthodontic Journal of Nepal, 2014)
Introduction: Bonding of the teeth with brackets have eased the orthodontic procedure. However the bonding of molars is not very successful because of the occlusal force, difficulty in moisture control and age factor. Banding is usually the safe option which is again associated with gingival problems. Objective: To compare the molar band height with that of adolescent maxillary molar height. Materials & Method: A total of 33 maxillary adolescent casts and 30 average sized molar bands were retrieved from the orthodontic clinic of Kathmandu University Hospital. The height of the tooth as well as molar band were measured at 4 different points: mesio-buccal (MB), disto-buccal (DB), mesio-palatal (MP), disto-palatal (DP) and compared with independent t-test by SPSS software. p-value was kept at 0.01 for significance. Result: There is no any statistical significant difference between the tooth and band heights at MB, DB and DP points. The difference is found on only one point MP which is statistically significant. Conclusion: There is a need of separate molar bands for adolescent patients. The band dimension should be reduced occluso-cervically to avoid gingival impingement.